Family relationships of the enigmatic rosid genera Barbeya and Dirachma from the Horn of Africa region (1997)
Abstract: Barbeya is a monotypic genus in the Horn of Africa and adjacent patts of Arabia. It is usually treated as the family Barbeyaceae and regarded as an aberrant member of Urticales. Dirachma, with one species on Socotra and one in Somalia, is usually treated as the family Dirachmaceae, in GeraniaIes, but a position in MaIvales has also been suggested. Analyses of molecular data, from both rbcL and trnL-F, indicate that Barbeya and Dirachma are closely related inter se as well as to Rhamnaceae and Elaeagnaceae. In an analysis based on morphology Barbeya groups with Elaeagnaceae, and Dirachma with Rhamnaceae and Ulmaceae. In a combined molecular and morphological analysis Barbeya is the sister group of Elaeagnaceae and Dirachma is the sister group of the whole BarbeyaElaeagnaceae-Rhamnaceae clade. However, the support for these arrangements is weak and, rather than merging Barbeyaceae with Dirachmaceae as suggested by the molecular analysis or with Elaeagnaceae as suggested by the morphological and combined analyses, it seems best to retain both Barbeyaceae and Dirachmaceae in their present circumscriptions, but in both cases in completely new positions in the angiosperm system. The results are compatible with a new circumscription of Rhamnales comprising Rhamnaceae, Elaeagnaceae, Dirachmaceae and Barbeyaceae.